Zonasi Potensi Airtanah Akuifer Bebas Di Cekungan Airtanah Majenang, Kabupaten Cilacap, Jawa Tengah - Mahira Anaqah Huwaina; Thomas Triadi putranto; Narulita Santi (PROMINE, 2017)
Majenang Groundwater Basin is located in Cilacap Regency, Central Java. There is an increase of itsusage every year. Because of that, it is necessary to make groundwater zonation to get an overview ofthe potential zonation, specifically in unconfined aquifer. The methods used in this study is measuringwater table, sampling 17 samples of groundwater and pumping test to get the quantity of groundwater.Based on the measurement of known water table, it flows from the side of basin to the center of basin.It has a value of water level between 0.1-4.5 mbgl and water table 33.3-119.9 masl. Pumping test dataprocessing generates characteristic data aquifers, with value of transmisivity (T) is 2.9-11.3 m2/day,hidrolic conductivity (K) is 0.7-4.9 m/day, maximum debit is 2.3-3.6 L/day and optimum debit is 2.0-2.9L/day. Based on the result of quantity data, it has a medium potential zone for the unconfined aquifer.